Experimental Investigation on Friction Coefficient of Composite Materials Sliding Against SS 201 and SS 301 Counterfaces - Nuruzzaman, D. M.; Chowdhury, M. A.; M. M., Rahman; Kowser, M. A.; Roy, B. K. (Elsevier Ltd, 2015)
In this research, friction coefficients of composite materials such as gear fiber reinforced plastic (gear fiber) and glass fiber reinforced plastic (glass fiber) are investigated and compared. In the experiments, gear fiber and glass fiber slide against different austenitic stainless steels such as stainless steel 201 (SS 201) and stainless steel 301 (SS 301). Experiments are carried out at low loads 2, 4 and 6 N, low sliding velocities 0.2, 0.4 and 0.6 m/s and relative humidity 70%. The obtained results reveal that in general, friction coefficient of gear fiber and glass fiber increases with the increase in normal load and sliding velocity. Results show that friction coefficient of glass fiber-SS 201 pair is the highest and gear fiber-SS 301 pair is the lowest within the observed range of normal load and sliding velocity. On the other hand, it is found that friction coefficient of glass fiber-SS 301 pair is slightly higher than that of gear fiber-SS 201 pair. During the running-in process, friction coefficient of gear fiber and glass fiber steadily increases with the increase in rubbing time and after certain duration of rubbing, it remains constant regardless of the counterface material. The obtained results reveal that for the observed range, the influence of normal load on the frictional properties of gear fibe and glass fiber is greater than that of sliding velocity. At identical operating conditions, the magnitudes of friction coefficient of gear fiber and glass fiber are different depending on normal load, sliding velocity and counterface material.